PERAN PENYULUH PERTANIAN DALAM MENGEMBANGKAN PENDAPATAN KELOMPOK TANI PADI SAWAH DI DESA DAMAI MAKMUR KECAMATAN NUHON - Labedi, Rifal; Zaenuddin, Ruslan A; Rustiawati, Yuni; Yatim, Hertasning (Fakultas Pertanian Universitas Tompotika Luwuk, 2024)
Agricultural extension is non-formal education provided to farmers and their families. The purpose of this study is to know and describe the role of agricultural extension workers and income in Damai Makmur Village, Nuhon District. This research was carried out in Damai Makmur Village, Nuhon District, from July to September 2023. The population that is the object of this study is a group of rice farmers in Damai Makmur Village, Nuhon District. There are 15 farmer groups, each group with 15 members. The sampling method in the study was purposive sampling (intentionally) and the samples taken in this study were 25 people. The results showed that the role of agricultural extension workers in developing the income of rice farmer groups has carried out 5 most important tasks, namely the role of extension workers as educators with a sufficient category of 69.6%, the role of extension workers as motivators with sufficient categories of 74.4%, the role of extension workers as dynamicators with sufficient categories of 68%, the role of extension workers as facilitators with good categories of 80%, the role of extension workers as innovators with good categories of 86.4%. This can show that the role of extension workers needs to be increased again in order to create quality and qualified farmers. As well as the income of farmers in Damai Makmur Village, Nuhon District, obtained from the reduction between Total Revenue (TR) of IDR 22,800,000 and Total Cost (TC) of IDR 6,822,500, then farmer income of IDR 15,977,500. Therefore, rice farming in Damai Makmur Village, Nuhon District, can continue to be developed by farmers.